Clinical Data Reuse or Secondary Use: Current Status and Potential Future Progress - Meystre, S. M.; Lovis, C.; Bürkle, T.; Tognola, G.; Budrionis, A.; Lehmann, C. U. (Yearbook of Medical Informatics, 2017)
Objective: To perform a review of recent research in clinical data reuse or secondary use, and envision future advances in this field.Methods: The review is based on a large literature search in MEDLINE (through PubMed), conference proceedings, and the ACM Digital Library, focusing only on research published between 2005 and early 2016. Each selected publication was reviewed by the authors, and a structured analysis and summarization of its content was developed.Results: The initial search produced 359 publications, reduced after a manual examination of abstracts and full publications. The following aspects of clinical data reuse are discussed: motivations and challenges, privacy and ethical concerns, data integration and interoperability, data models and terminologies, unstructured data reuse, structured data mining, clinical practice and research integration, and examples of clinical data reuse (quality measurement and learning healthcare systems).Conclusion: Reuse of clinical data is a fast-growing field recognized as essential to realize the potentials for high quality healthcare, improved healthcare management, reduced healthcare costs, population health management, and effective clinical research.
Keywords: Medical informatics; electronic health records; health services research; health care evaluation mechanisms; clinical studies as topic